The Effect of Mycotoxins and Silymarin on Liver Lipidome of Mice with Non-Alcoholic Fatty Liver Disease - Bechynska, Kamila; Kosek, Vit; Fenclova, Marie; Muchova, Lucie; Smid, Vaclav; Suk, Jakub; Chalupsky, Karel; Sticova, Eva; Hurkova, Kamila; Hajslova, Jana; Vitek, Libor; Stranska, Milena (Biomolecules, 2021)
Milk thistle-based dietary supplements have become increasingly popular. The extract from milk thistle (Silybum marianum) is often used for the treatment of liver diseases because of the presence of its active component, silymarin. However, the co-occurrence of toxic mycotoxins in these preparations is quite frequent as well. The objective of this study was to investigate the changes in composition of liver lipidome and other clinical characteristics of experimental mice fed by a high-fat methionine-choline deficient diet inducing non-alcoholic fatty liver disease. The mice were exposed to (i) silymarin, (ii) mycotoxins (trichothecenes, enniatins, beauvericin, and altertoxins) and (iii) both silymarin and mycotoxins, and results were compared to the controls. The liver tissue extracts were analyzed by ultra-high performance liquid chromatography coupled with high-resolution tandem mass spectrometry. Using tools of univariate and multivariate statistical analysis, we were able to identify 48 lipid species from the classes of diacylglycerols, triacylglycerols, free fatty acids, fatty acid esters of hydroxy fatty acids and phospholipids clearly reflecting the dysregulation of lipid metabolism upon exposure to mycotoxin and/or silymarin.
Keywords: Non-alcoholic Fatty Liver Disease; Silymarin; mycotoxins; Mycotoxins; Male; Lipidomics; lipidomika; lipidome; mass spectrometry; mužské pohlaví; metabolismus lipidů; silymarin; mice liver; Animals; nealkoholová steatóza jater; játra; metabolome; zvířata; Lipid Metabolism; myši inbrední C57BL; myši; Mice, Inbred C57BL; Liver; Mice; mykotoxiny